2010
DOI: 10.1590/s1413-70542010000400021
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de fungos toxigênicos e aflatoxinas em arroz

Abstract: RESUMOUm dos problemas mais sérios que confrontam a qualidade do arroz é a presença de fungos produtores de micotoxinas, principalmente as espécies pertencentes aos gêneros Aspergillus, Penicillium e Fusarium. Neste estudo, objetivou-se verificar os níveis de aflatoxinas e identificar a população fúngica associada a grãos de arroz beneficiado e comercializado em Belo Horizonte e algumas cidades do sul do estado. Foram analisadas um total de 60 amostras de arroz: orgânico, parboilizado, integral, polido, sendo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…The fungal deterioration potential and the lower grain quality and yield has guided the search of new techniques to control and reduce infestations, including the adoption of good practices on farming and during drying and storage of grains (CARVALHO et al, 2010), planting more resistant cultivars , and use of new pesticides . In addition, it is necessary to focus on acceptable levels for the occurrence of FB1, not only by the requirement of importing countries but also to minimize the risks to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…The fungal deterioration potential and the lower grain quality and yield has guided the search of new techniques to control and reduce infestations, including the adoption of good practices on farming and during drying and storage of grains (CARVALHO et al, 2010), planting more resistant cultivars , and use of new pesticides . In addition, it is necessary to focus on acceptable levels for the occurrence of FB1, not only by the requirement of importing countries but also to minimize the risks to consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxins may occur in peanuts, corn (maize) and cottonseed, as well as in many other agricultural commodities ( Pittet 2001 ). Occurrence in rice has also been reported in a number of countries ( Reddy et al 2008 ; Gummert et al 2009 ): Sri Lanka ( Bandara et al 1991 ), Bangladesh ( Dawlatana et al 2002 ), Japan ( Tabata et al 1993 ), China ( Liu and Gao 2006 ; Wang and Liu 2007 ), Vietnam ( Nguyen et al 2007 ), Thailand ( Shank et al 1972 ), India ( Pande et al 1990 ; Toteja et al 2006 ; Reddy et al 2009 ), the Philippines ( Sales and Yoshizawa 2005 ), Korea ( Park et al 2004 , 2005a ), United Arab Emirates ( Osman et al 1999 ), Turkey ( Aydin et al 2010 ), Tunisia ( Ghali et al 2008 ), Nigeria ( Hussaini et al 2007 ), Côte d'Ivoire ( Sangare-Tigori et al 2006b ), Uruguay ( Piñeiro et al 1996 ), Brazil ( Soares and Rodriguez-Amaya 1989 ; de Carvalho et al 2010 ), and the United States ( Abbas and Shier 2009 ), as well as in imported/ marketed rice in the United Kingdom ( Scudamore et al 1998 ; Food Standards Agency (FSA) 2002 ), Austria ( Reiter et al 2010 ), Iran ( Mazaheri 2009 ) and Sweden ( Fredlund et al 2009 ; Nordkvist et al 2009 ). The study in Vietnam indicated that the rainy season was a major risk factor for occurrence of AFB 1 in rice ( Nguyen et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Hirota et al, (2012), o ensaio de letalidade frente à A. salina é uma metodologia muito utilizada para avaliar o potencial tóxico de extratos e substâncias isoladas. Ela é utilizada em testes de toxicidade aguda devido à sua capacidade para formar cistos dormentes, sua praticidade de manuseio e cultivo, por ser um método rápido e barato, aplicável como bioindicador em uma avaliação toxicológica pré-clínica (CARVALHO, et al;. Devido á estas características, esta metodologia vêm sendo empregada além da linha de pesquisa em produtos naturais, sendo observada sua aplicabilidade em áreas como síntese de medicamentos, farmacologia, neurologia, química, meio ambiente, ecologia, screening biológico e outros (HIROTA et al, 2012).…”
Section: Introductionunclassified